2018
DOI: 10.25300/misq/2018/13575
|View full text |Cite
|
Sign up to set email alerts
|

Governance of Corporate Takeovers: Time for Say-on-Takeovers?

Abstract: We study the potential for digital, online information and electronic voting to improve shareholder surplus by facilitating a new governance structure: owner-governance, which shifts control of the takeover decision from the board to shareholders. We compare analytical models of owner-governance to the current practice of delegated-governance in the context of increasing availability of online information which increases public informedness. Our analysis shows that shareholders of the target firm and the acqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…An international examination of corporate governance found that governance affects shareholder wealth (Aggarwal et al, 2007). Academic research supports the conclusion that transferring power from boards to shareholders increases existing shareholder wealth (Vithayathil and Shiv-endu, 2019;Vithayathil and Choudhary, 2018, Bebchuk, 2002, 2004.…”
Section: The Decline Of Corporate Governance Within Public Companiesmentioning
confidence: 87%
See 1 more Smart Citation
“…An international examination of corporate governance found that governance affects shareholder wealth (Aggarwal et al, 2007). Academic research supports the conclusion that transferring power from boards to shareholders increases existing shareholder wealth (Vithayathil and Shiv-endu, 2019;Vithayathil and Choudhary, 2018, Bebchuk, 2002, 2004.…”
Section: The Decline Of Corporate Governance Within Public Companiesmentioning
confidence: 87%
“…Measures such as staggered boards, poison pills, supermajority requirements, and others act together to entrench boards. Striking evidence from research supports the conclusion that entrenchment of boards is harmful to shareholders (Vithayathil and Choudhary, 2018;Gompers, Ishii, and Metrick, 2003;Bebchuk, Cohen, and Ferrell, 2008). Entrenchment is one way to frame weak corporate governance.…”
Section: The Decline Of Corporate Governance Within Public Companiesmentioning
confidence: 95%